2019 IEEE 16th International Conference on Mobile Ad Hoc and Sensor Systems (MASS) 2019
DOI: 10.1109/mass.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

System Level Analysis for ITS-G5 and LTE-V2X Performance Comparison

Abstract: Vehicular communications, known under the name of V2X (Vehicle to Everything) are expected to grow fast in the next years, bringing for example safer driving conditions, optimized traffic management, energy reduction, etc.. Currently two short range-based technologies (ITS-G5, standardized in Europe by ETSI and derived from WiFi communications IEEE standards and LTE based Vehicle to Everything or LTE-V2X developed by 3GPP and derived from LTE) consider the use of 5.9 GHz ITS band for their deployment. While di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Number: [1,3,5,10,15,20] Size: [4,5,6,8,9,10,12,15,16,18,20,25,30,48,50 In LTE-V2X mode 4, the selection of radio resources is performed within a period, set in the interval [20...100] ms, according to the requirements of the previous layers, called the selection window. It is defined as [n+T1, n+T2] where n is the instant at which the vehicle makes the decision for a new resource allocation, 1≤ T 1 ≥ 4 and 20 ≤ T 2 ≥ 100 (T1 and T2 are selected by the vehicle).…”
Section: A Resources Grid and Frame Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Number: [1,3,5,10,15,20] Size: [4,5,6,8,9,10,12,15,16,18,20,25,30,48,50 In LTE-V2X mode 4, the selection of radio resources is performed within a period, set in the interval [20...100] ms, according to the requirements of the previous layers, called the selection window. It is defined as [n+T1, n+T2] where n is the instant at which the vehicle makes the decision for a new resource allocation, 1≤ T 1 ≥ 4 and 20 ≤ T 2 ≥ 100 (T1 and T2 are selected by the vehicle).…”
Section: A Resources Grid and Frame Structurementioning
confidence: 99%
“…The papers [14], [15], [8], [16] present comparisons of the LTE-V2X performance with that of ITS-G5. Cecchini et al has shown in [14] that in a scenario characterized by a congested highway, the LTE-V2V mode 3 always outperforms ITS-G5 and LTE-V2V mode 4 regarding PRR, and that ITS-G5 provides better performance than LTE-V2V mode 4 for short communication distances.…”
Section: B Lte-v2x Mode 4 Comparison With Existing Vehicular Technolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…OpenCV2X has been fully validated against [5] to ensure correctness of the model. Existing research published in [7], [8] use custom system level simulators but these are not available to the wider vehicular communications community limiting reproducibility. To the best of the authors knowledge, there exists only 2 system level simulators [9], [10], intended for contribution to the wider research community.…”
Section: A Simulation Modelsmentioning
confidence: 99%
“…This simulating approach is referred to as "system level simulation" [4] and it is detailed in Section III. However this approach also requires physical layer simulations to be carried out, as described in Section II.…”
Section: Introductionmentioning
confidence: 99%